The Role of Social Media in Enhancing Students' Extrinsic Social and Instrumental Motivation in German Learning - Kristianto, Adam Juliano; Shohibu Zaman; Zahra Dinda Rodistya; Herri Akhmad Bukhori (Nexus Publishing NXP, 2025)
This study aims to describe the role of social media in increasing students' extrinsic motivation, both in the social and instrumental categories, in learning German. Through a descriptive quantitative approach, data were collected from 51 student respondents who are active users of social media who have attended German language courses for at least one semester. A 5-point Likert scale questionnaire was used to measure three main variables, namely intensity of social media use, instrumental extrinsic motivation, and social extrinsic motivation. The results show that platforms such as Instagram and TikTok are significantly utilized by students as a means of self-learning, expanding vocabulary, and strengthening social connections with online learning communities. Social media is also proven to support learning that is more flexible, interesting and relevant to the digital needs of today's students. This finding confirms that social media has great potential as an additional learning medium that can externally motivate students, both for social (community acceptance) and instrumental (career and academic development) purposes.